KESANTUNAN BERBAHASA DALAM PANTUN SEUMAPA (KAJIAN MAKSIM MENURUT GEOFFREY LEECH) - Junaidi Junaidi; Razali Razali; Siti Sarah Fitriani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aims to describe the politeness of language in all pantun based on (1) wisdom maxims; (2) the maxim of generosity; (3) the maxim of reward; (4) the principle of praise / simplicity; (5) consensus maxim; and (6) sympathy principle. The data in this study are utterances in poetry which are categorized as polite if they are in accordance with the maximum assessment indicators and are categorized as impolite if they violate the maximum assessment indicators. Data collection techniques used in this study were observation techniques, recording techniques and data reduction. The data analysis techniques used were: (1) identifying the maxims in each speech data; (2) clarify the speech data from the identification results based on the maxims of politeness; (3) analyzing speech data based on the criteria for assessing the politeness of leech theory learning; (4) describe the results of the analysis of speech data into the principle of leech politeness. The results showed that there were utterances that met the maximum assessment criteria and some violated Leech's maxims of politeness. The descriptions are detailed as follows: (1) Based on the wisdom maxim, 3 expressions that fulfill the maxim and 2 words that violate the maxim are found; (2) maxim of generosity, found 11 data that obey the adage and no data that violates; (3) maxim reward found 7 data that violated the maxim and 1 data violated the maxim; (4) simplicity maxims, found 4 data that obey the maxims and 2 data that violate the maxims; (5) maxim of consensus, it was found that 4 data were in accordance with the maxims and there were no violating data; (6) proverbial conclusions, found 3 data that is obedient and no data that violates.